IDEOLOGY OF BHAGAT SINGH WITH SPECIAL REFERENCE TO INDIA'S FREEDOM STRUGGLE - Khalid Bashir; Ishfaq Ahmad Mir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Bhagat Singh, a prominent freedom fighter and revolutionary from India, played a crucial role in India's struggle for independence from British colonial rule. His ideology was shaped by a deep sense of patriotism, a firm belief in socialism, and a desire for social equality and justice. This research paper aims to provide an in-depth analysis of Bhagat Singh's ideology, with a special focus on its relevance to India's freedom struggle. It explores the key principles of Bhagat Singh's ideology, his motivations, and the impact of his ideas on the Indian freedom movement. Additionally, this paper examines Bhagat Singh's contributions to the anti-colonial struggle, his methods of protest, and the legacy he left behind as a martyr for the cause of Indian independence.